2017
DOI: 10.1111/1440-1630.12397
|View full text |Cite
|
Sign up to set email alerts
|

Mental health education in occupational therapy professional preparation programs: Alignment between clinician priorities and coverage in university curricula

Abstract: While there appears to be overall good alignment between mental health curricula and priorities identified by practising occupational therapists, there are some discrepancies. These discrepancies are described and establish a strong foundation for further discussion between clinicians, academics and university administration to support curriculum review and revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Participants appeared to value the professional practice knowledge of occupations and participation, and a therapy focus on understanding and addressing difficulties in performing occupations and the practical supports necessary to re-engage in occupations. This appears to match with a strong emphasis on occupation-focused therapy by occupational therapists, educators and researchers (D’Amico et al., 2018; Hitch and Lhuede, 2015; Kannenberg, 2010; Scanlan et al., 2015, 2017; Wimpenny et al., 2014). This issue warrants further research and greater attention in pre-registration education.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Participants appeared to value the professional practice knowledge of occupations and participation, and a therapy focus on understanding and addressing difficulties in performing occupations and the practical supports necessary to re-engage in occupations. This appears to match with a strong emphasis on occupation-focused therapy by occupational therapists, educators and researchers (D’Amico et al., 2018; Hitch and Lhuede, 2015; Kannenberg, 2010; Scanlan et al., 2015, 2017; Wimpenny et al., 2014). This issue warrants further research and greater attention in pre-registration education.…”
Section: Discussionmentioning
confidence: 89%
“…There is limited alignment between these lived experience-informed capabilities and professionally defined curriculum priorities (Scanlan et al., 2015, 2017). Participants in this study identified five important types of knowledge, but most importantly emphasised the critical importance of holding these in balance and integrating knowledge frameworks.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in line with what other authors have stated about the importance of exploring in the curriculum. Based on the strategies that students adopt for correct performance in professional practice, along with the strategies that allow them to develop their resilience in the professional context (Scanlan et al, 2017 ). In accordance with the above mentioned, the aim of the present study was to determine whether there is an improvement in the resilience of students of occupational therapy after their first exposure to practice placement education.…”
Section: Introductionmentioning
confidence: 99%